STUDIES ON PHYSICO-MORPHOLOGICAL CHARACTERISTICS AND FERTILIZING ABILITY OF SEMEN OF TARAI BUFFALO BULLS - SINGH, BEERENDRA; GUPTA, H P; SAXENA, M S (The Indian Journal of Animal Reproduction, 2011)
A total of 60 semen ejaculates were collected from six Tarai buffalo bulls using sterilized artificial vagina twice weekly. The ejaculates were evaluated and characterized for various physico-morphological characteristics as well as in-vitro fertility using hypo-osmotic swelling and poly-acrylamide gel penetration tests. The ejaculate volume, pH, sperm mass motility, progressive motility, density, livability, head, mid piece, tail and total abnormalities, acrosomal integrity and methylene blue reduction time in Tarai buffalo bulls were 3.25±0.12 ml, 6.79±0.02, 4.180±.03. 83.66±0. 71%, 1289.83±51.64 million/ml, 92. 70±.50%, 1.520±.08%, 1.120±.04%,3.85±0.18%,6.48±.22%,95.86±0.24 %, 6.36±0.28 minutes, respectively.The hypo-osmotic swelling percent and poly-acrylamide gel penetration distance were 77.420±. 73 per cent and 25.50±0.44 mm/hr, respectively. It was concluded that quality of semen was good and physico-morphological characteristics were in the normal range described for the buffalo, hence may be utilized for freezing and further use in propagation and development of the Tarai buffalo.